« LE PAYS DU CHOCOLAT » DE ROSETTA LOY Poétique d’un conte fait-diversier - Mahy, Fanny (2018)
2005, Novi Ligure, Italy. A teenager helped by her boyfriend stabs her mother and little brother. Inspired by this fact, "Le Pays du Chocolat" is published in 2010 and is the first tale of the little book Cuori infrantiby the Italian writer Rosetta Loy.The purpose of this article is to bring to light the cameleoneous travesty of the news item, that is to say its passage from the media narrative to the tale-diversier story. The classic tools of narratology are convened to conduct an analysis of some of the most significant elements and processes of this hybrid and singular poetics, which borrows at the same time from the media narrative, the tale and the short story.